Microstructures and Mechanical Properties of Nanocrystalline AZ31 Magnesium Alloy Powders with Submicron TiB2 Additions Prepared by Mechanical Milling - Haiping Zhou; Chengcai Zhang; Baokun Han; Jianfeng Qiu; Shengxue Qin; Kuidong Gao; Jie Liu; Shuai Sun; Hongbin Zhang (Crystals, 2020)
In this work, nanocrystalline AZ31 magnesium alloy powders, reinforced by submicron TiB2 particles, were prepared via mechanical milling. It was found that TiB2 particles stimulated the fracture and welding of AZ31/TiB2 powders, leading to the acceleration of the milling process. Meanwhile, the TiB2 particles were refined to submicron-scale size during the milling process, and their distribution was uniform in the Mg matrix. In addition, the matrix was significantly refined during the milling process, which was also accelerated by the TiB2 particles. The formation of grain boundary segregation layers also led to the weakened TiB2 peaks in the XRD patterns during the mechanical milling. The grain sizes of AZ31–2.5 wt % TiB2, AZ31–5 wt % TiB2 and AZ31–10 wt % TiB2 powders were refined to 53 nm, 37 nm and 23 nm, respectively, after milling for 110 h. Under the combined effect of the nanocrystalline matrix and the well-dispersed submicron TiB2 particles, the AZ31/TiB2 composites exhibited excellent micro-hardness. For the AZ31–10 wt % TiB2 composite, the micro-hardness was enhanced to 153 HV0.5.